2010
DOI: 10.1111/j.1365-263x.2010.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dental fear in French children aged 5–12 years

Abstract: This study shows that for children aged 5-12 years, prior experience of the dental setting can act as a positive component of dental fear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
85
3
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 30 publications
13
85
3
19
Order By: Relevance
“…Although there is a strong correlation between anxiety and caries experience, inasmuch as studies show that children who present low dmft scores (0-3) are less anxious than those with medium (4-6) and high (≥7) dmft scores (NICOLAS et al, 2010;OLAK et al;2013), the present study strictly observed the volunteer selection criteria, considering tooth and cavity-related characteristics, resulting from the variables studies and the "splitmouth" design and, accordingly, the children presented with the same pattern of caries severity, which may not have interfered with the results. The intervention by the assistant when explaining the restorative techniques to the children, prior to the application of the FIS scale and the use of the frequency meter, may have interfered with anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a strong correlation between anxiety and caries experience, inasmuch as studies show that children who present low dmft scores (0-3) are less anxious than those with medium (4-6) and high (≥7) dmft scores (NICOLAS et al, 2010;OLAK et al;2013), the present study strictly observed the volunteer selection criteria, considering tooth and cavity-related characteristics, resulting from the variables studies and the "splitmouth" design and, accordingly, the children presented with the same pattern of caries severity, which may not have interfered with the results. The intervention by the assistant when explaining the restorative techniques to the children, prior to the application of the FIS scale and the use of the frequency meter, may have interfered with anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nicolas et al concluded that children who needed to undergo, at the very least, a restorative procedure, had a greater fear of the dentist when compared to children with no need for treatment (18) .…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients are still afraid of the dentist 14 . Fear of dental treatment has been recognized as one of the leading problems in pediatric dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the above studies did not observe significant association between age and dental anxiety 3,19 . The influence of age on anxiety during dental treatment is still unclear, since few studies have investigated this topic 14 .…”
mentioning
confidence: 99%